Chameleon aura - Chapata, Billy (Andrews McMeel Publishing, 2019)
"Zimbabwean poet Billy Chapata provides a thought-provoking take on the universal experiences of love, pain, and what comes next through messages of empowerment. This collection of poetry and prose will justify heartache and inspire the fortitude to survive and prosper."--Publisher's description.